Dampak Penggunaan Media Sosial terhadap Tingkat Perilaku Kenakalan Remaja di Era Digital Saat Ini - Nilot Pramudita; Nailla Rafa; Panji Utomo; Kukuh Hussein; Ken Ayu (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
The use of social media has become an inseparable part of daily life for Indonesian teenagers. Platforms such as Instagram, TikTok, and WhatsApp are widely used for communication, self-expression, entertainment, and information. However, behind these benefits lie significant negative impacts, particularly the rise of juvenile delinquency and digital violence. Phenomena such as cyberbullying, the spread of negative content, hoaxes, hate speech, and online exploitation are increasingly prevalent. Data from GoodStats and the 2024 National Survey on the Life Experiences of Children and Adolescents (SNPHAR) reveal high rates of violence experienced and perpetrated by teenagers in digital spaces. Furthermore, reports from the Indonesian Child Protection Commission (KPAI) show a yearly increase in cases of juvenile misbehavior linked to social media usage. This study employs a descriptive quantitative approach using secondary data from KPAI, GoodStats, and SNPHAR. The objective is to identify various forms of juvenile delinquency triggered by social media use and to explore both existing and potential strategies for prevention. The analysis indicates that low levels of digital literacy among teenagers, weak parental supervision, and the influence of social media algorithms that often amplify extreme content are major contributing factors to deviant behavior. This research emphasizes the importance of collaborative efforts among families, schools, the government, and digital platforms to create a safe and healthy digital environment for teenagers. Comprehensive digital literacy education, character development, stronger child protection regulations on the internet, and increased parental involvement are key strategies that need to be strengthened. Through an integrated approach, it is hoped that the risks of delinquency and digital violence can be minimized, enabling Indonesian youth to grow into a generation that is intelligent, critical, and responsible in their use of social media.